O contraste entre oclusivas alveolares e velares: estados gradientes mediados por análise acústica e ultrassonográfica - Melo, Roberta Michelon (2016)
The Brazilian Portuguese stops sounds present unique characteristics in relation to acoustic and articulatory aspects. These consonants differ from each other by voicing and place of articulation. In some cases of phonological disorders, it is observed phonic instability during the production of the contrast between the alveolar and velar stops, target segments of this thesis. In these cases, speech instrumental analysis, such as acoustic and articulatory (e.g. ultrasound tongue images) may identify speakers undetected linguistic skills through auditory perceptual analysis. In order to help data interpretation, this study was based on the Gestural Phonology theoretical perspective. Thus, the general purpose of this study was to identify evidence of articulatory refinement during typical speech development and to examine the presence of phonic contrasts under construction (covert contrasts) in speech of children with phonological disorders. In this regard, this study sample consisted of 20 adults and 15 children with typical speech development and seven children with phonological disorders. The speech collection consisted of naming representative pictures of the target-words, into carrier phrases. Simultaneous recording of audio and video data was performed through the Articulate Assistant Advanced Software. The data analysis occurred through acoustic analysis (parameters: voice onset time; spectral peak and burst spectral moments; vowel/consonant transition and relative duration measures of the burst and of the occlusion) and articulatory (parameters: proportion of significant axes of the tongue anterior and posterior region and description of tongue curves). It was also performed speech therapy for the three children with phonological disorders; two of them were submitted to therapeutic procedures through ultrasound tongue images visual feedback and one without visual feedback support. The analysis of the therapeutic effects was performed through the same articulatory parameters and through auditory perceptual analysis. About the main study results: (i) It was suggested a period of stabilization during typical speech development, even after the complete sounds acquisition; (ii) it was also verified evidence of gradient condition and covert contrasts in speech of the children with phonological disorders, and; (iii) the proposed speech therapy and its therapeutic procedures were effective to acquisition and stabilization of the contrast between alveolar and velar stops. However, the use of the visual feedback therapeutic resource did not present strong evidence of superiority of this technique in opposition to not using it, unless through the results of auditory and articulatory perceptual analysis used in this study. Also in relation to speech therapy, the articulatory analysis through ultrasound images was not more sensitive in the understanding of gradient conditions during the therapeutic process in relation to auditory perceptual analysis. So, although some research hypotheses were partially proven, it is believed in the present study contribution to understand the complexity involved in speech development, as typical, as with alterations. From this, there is the intention of instigating new questions and directions to Speech, Language and Hearing Sciences.